Motyw krwi w poezji Inny Lisnianskiej - Nikadem-Malinowska, Ewa (Acta Polono-Ruthenica, 2011)
Inna Lisnianskaya is a Russian poet who has been continuously writing since the fifties and the author of hundreds outstanding poems. She has built her poetic universe on the basis of certain concepts. Some of them appear more often than the others and blood is one of them. About a hundred of Inna Lisnianskayas poems that include the motif of blood was chosen for this work. Their analysis (in accordance to the studies of R. W. Langaker) is to show that the phenomenon of subjectification is the basis of the conceptualization process.